Project More Doctors for Brazil in remote areas of the state of Roraima: relationship between doctors and the Special Supervision Group - Willian Fernandes Luna; Bruna Teixeira Ávila; Carlos Fabrício Fernandes Brazão; Fernanda Pereira de Paula Freitas; Luciana Côrrea de Sena Cajado; Luiz Otávio de Araújo Bastos (Faculdade de Medicina de Botucatu (Unesp), 2019)
ABSTRACT This article aims at discussing aspects of the Project More Doctors for Brazil's Special Supervision Group in areas of difficult access in the Brazilian state of Roraima. It is focused on the relationships between supervisors and doctors, identifying potentialities and difficulties, and highlighting strategies to overcome them. This is an experience report from a thematic content analysis of documents produced by supervisors in 2015 and 2016. Three key categories emerged: potentialities, challenges of the process and constructions based on supervision. Based on the analysis, this is an innovative relationship in healthcare, where academia and services hardly ever come together. It is a complex relationship with structural, cultural and educational limitations. It requires creativity and planning to play all different roles under construction.